2001
DOI: 10.1021/bm010097x
|View full text |Cite
|
Sign up to set email alerts
|

Terminally Alkylated Heparin. 2. Potent Antiproliferative Agent for Vascular Smooth Muscle Cells

Abstract: The antiproliferative activity of alkylated heparin, in which the terminal end of heparin is derivatized with an alkyl group (butyl, octyl, lauryl, stearyl), was examined using vascular smooth muscle cells. The proliferation of cells, which were growth-arrested prior to addition of heparin, was inhibited in proportion to both increase in the chain length of the alkyl group of alkylated heparin and alkylated heparin concentration in the serum-containing medium. The antiproliferative activity of stearyl group de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…It was found that chitosan-g-PEG was non-toxic to the cancer cells, indicating that the cationic polymer itself was not responsible for the cell death. Since heparin is a highly negatively charged macromolecule, the absorptive endocytosis of heparin across the cell membrane would not occur (26). It was most likely that the chitosan-g-PEG/heparin polyelectrolyte complex micelles entered the cell by nonspecific adsorptive endocytosis, inducing the cancer cell death more efficiently than free heparin alone.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that chitosan-g-PEG was non-toxic to the cancer cells, indicating that the cationic polymer itself was not responsible for the cell death. Since heparin is a highly negatively charged macromolecule, the absorptive endocytosis of heparin across the cell membrane would not occur (26). It was most likely that the chitosan-g-PEG/heparin polyelectrolyte complex micelles entered the cell by nonspecific adsorptive endocytosis, inducing the cancer cell death more efficiently than free heparin alone.…”
Section: Resultsmentioning
confidence: 99%
“…Periodate-oxidized heparin fragments were converted to the tributylammonium salt using a modification of previously described conditions. 17,18 Briefly, heparin fragments (10 g) were dissolved in water (50 mL) and passed through a column (300 mL) of Dowex 50WX8 (H + ) cation-exchange resin. The pH of the eluent ($500 mL) was adjusted to pH 6.0 using Bu 3 N ($25 mL, 0.1 mol).…”
Section: 22mentioning
confidence: 99%
“…The derivatives of tributylammonium salt of periodate oxidized heparin fragments were acylated with hexanoic anhydride using a modification of methods previously described. 17,18 Briefly, the dry tributylammonium salt (12 g), dissolved in dry DMF (110 mL) was cooled to 0°C under an argon atmosphere. 4-Dimethylaminopyridine (0.7 g, 5.7 mmol), hexanoic anhydride (26.2 mL, 0.1 mol), and Bu 3 N (27 mL, 0.1 mol) were successively added in single portions, and the reaction was allowed to proceed under Ar at room temperature for 24 h. After cooling to 0°C, 5% NaHCO 3 in water (230 mL) was gradually added, and the solution was stirred at room temperature for 48 h. Excess NaHCO 3 was eliminated by slow, dropwise addition of 1 N HCl ($200 mL) until a pH of 4.0 was reached, and then the pH was readjusted to 7.0 with 1 N NaOH ($150 mL).…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is still hard to determine the ultimate effect of heparin on cancer progression due to the wide variety of its physiological activities (2,4,10). Although several effective approaches for using sulfated oligosaccharides (11) or chemically modified heparins, such as polystyrene bearing and steroid conjugated heparin (12,13), terminally alkylated heparin (14), have been investigated as angiogenesis inhib-itors or anti-tumor agents, most of technologies were addressed on only angiogenesis, and they required high doses causing the negative effects discussed above.…”
Section: Introductionmentioning
confidence: 99%